(untitled) (KULT_online, 2022)
Postmigration has become a prominent concept within the Humanities. Postmigration: Art, Culture, and Politics in Contemporary Europe clarifies many questions circulating around the source of its ideas. The authors portray different approaches and lay out a chronology of the term´s multifaced interpretations. Elaborating its actual qualities along artistic objects and cultural spaces, the contributions of the volume provide a notion of postmigration that effectively negotiates complexities of the contemporary.